Three-dimensional modeling of the mechanical behavior of a single pile in unsaturated expansive soils during infiltration. (May 2022) - Wu, Xingyi; Vanapalli, Sai K.
Abstract: In this paper, a novel coupled hydro-mechanical model for unsaturated expansive soils and a constitutive model for unsaturated pile-soil interfaces are implemented into ABAQUS for performing 3-D finite element analysis of single piles in expansive soils during infiltration. Some key features of coupled thermal–mechanical model from ABAQUS are used to formulate coupled hydro-mechanical model developing five independent user-material subroutines. User-defined field subroutine (USDFLD) is used to access the stress and strain and transfer these values to other subroutines. Three subroutines including user-defined material subroutine (UMAT), user-defined thermal material subroutine (UMATHT), and user-defined thermal expansion subroutine (UEXPAN) are developed and used to calculate the stress-deformation, the hydraulic behavior, and the expansion strain, respectively. In addition, an unsaturated soil-structure interface model is implemented into user-defined friction behavior subroutine (FRIC) to calculate the friction stress between soil and pile. The program is successfully validated using experimental results performed on a single model pile in an expansive soil. The modeling results are consistent with the experimental results which suggest that a decrease in matric suction can contribute to the reduction in the shaft friction as more load is transferred to the pile resulting in an increase in the pile head settlement and pile base resistance. The modeling approach presented in this paper is promosing and can be extended by the practitioners in the rational design of pile foundations in expansive soils.